101k views
4 votes
What are the first three terms of the sequence defined by the following equation?

an = 2 • (-3)n - 1.

User Artgrohe
by
5.5k points

2 Answers

4 votes

Answer:

-7, -13, -19

Explanation:

plug in 1,2, and 3 into the part of the equation "n".

User Dog
by
5.3k points
0 votes

Answer:

a1 = -7

a2 = - 13

a3 = - 19

Explanation:

n = 1

a1 = 2*(-3)*1`- 1

a1 = -6 - 1

a1 = - 7

n=2

a2 = 2(-3)*2 - 1

a2 = -12 -1

a2 = - 13

n3 = 2(-3)*3 - 1

n3 = -18 - 1

n3 = -19

Each term is - 6 away from the previous one.

User Ando
by
6.0k points